The Influence of Leadership and Work Culture on Employee Performance at the Population Control and Family Planning Service of Karawang Regency - Ikhsan Ma'arif Munadi; Suroso Suroso; Dwi Epty Hidayati (Economics and Digital Business Review, 2026)
This study aims to analyze and explain how leadership and work culture influence employee performance at the Population and Family Planning Control Office (DPPKB) of Karawang Regency, both partially and simultaneously . Utilizing a verification method with a quantitative approach , the research involved the entire population of 38 employees as respondents through a saturated sampling technique . Data were collected via questionnaires and processed using multiple linear regression and hypothesis testing . The results partially indicate that leadership has a positive and significant effect on employee performance , with a significance value of 0.000 < 0.05 . Similarly , the work culture variable is proven to have a significant partial effect on performance . Simultaneously , leadership and work culture significantly influence employee performance with a 72% contribution , as indicated by an R Square value of 0.720 . In conclusion , strengthening leadership patterns and internalizing positive work values serve as key instruments in enhancing employee performance at DPPKB Karawang Regency to achieve established organizational targets .